FARMING OF NILE TILAPIA (Oreochromis niloticus) AT THE KRIDO YUWONO FARM IN PANEMBANGAN - Emyl Rohayati; Kasprijo (PT. Artha GenetikaLab Indonesia, 2026)
Tilapia farming is the practice of raising fish from fry to marketable size to meet increasing consumer demand. This study aims to evaluate tilapia farming activities at the Krido Yuwono Panembangan Fish Farming unit. The research methods employed were direct observation and active participation in all farming processes to obtain comprehensive and accurate data. The variables observed included farming stages, fish length and weight, survival rate (SR), specific growth rate (SGR), and feed conversion ratio (FCR). The farming activities consisted of several stages, including pond preparation (drying, liming, fertilization, and water filling), seed stocking, feeding management, and water quality control. The results showed that the survival rate reached 86.67%, indicating a relatively high level of fish survival during the culture period. The specific growth rate was recorded at 1.77% per day, while the feed conversion ratio was 1.35, reflecting efficient feed utilization. Overall, the applied farming practices were effective and supported optimal tilapia production.